The Situation and Counter Measures of Sports Development in New Rural Communities under the Strategy of Rural Revitalization in China - Yanhua Chen (Forest Chemicals Review, 2022)
In this study, we used the methods of literature review, questionnaire survey, interview and statistics to study the situation and restrictive factors of community sports in new rural communities in Jiangxi Province under the current rural revitalization strategy. Therefore, it was proposed that the countermeasures of the new rural community sports development in Jiangxi Province under the rural revitalization were to strengthen scientific sports propaganda, optimize the management system of rural sports, strengthen the construction of rural sports facilities, and develop sports projects with traditional characteristics such as nationality and locality, to create a diversified model of new rural community sports development.